A Description 0f the Level of Satisfaction of Family Planning (KB) Acceptors with Long-Term Contraceptive Method Services (MKJP)) - Assofi, A. Amanda Maharani; Saimin, Juminten; Yulia, Andi (Lombok Medical Journal, 2025)
Abstract. The increasingly discussed contraceptive method is the long-term contraceptive method, which offers safety, effectiveness, and comfort. However, the implementation of family planning services is still not optimal, as can be seen from the low participation in the MKJP. The prevalence of MKJP usage according to SDKI baseline data in 2019 is 21.39% while the 2024 RPJMN target is 28.39%. The thing that affects participation in participating in family planning is the satisfaction of the acceptor with the services of health facilities. This study was conducted to find out the overview of the level of satisfaction of family planning acceptors with MKJP services. This study uses a type of quantitative descriptive research. The number of samples in this study was 56 respondents of Women of Childbearing Age (WUS), data collection was obtained using questionnaires distributed to WUS who received MKJP family planning services at the Poasia Health Center, the data obtained will be analyzed using SPSS version 24 in the form of a frequency distribution table. The study's findings included satisfaction levels in the "very satisfied" category for the reliability dimension (83.2%), Assurance dimension (85.4%), Tangibles dimension (86.9%), empathy dimension (85.5%), and responsiveness dimension (85%). Overall, mothers who received MKJP family planning services at the Poasia Health Center felt "very satisfied" (85.4%) with the services provided by paying attention to the five dimensions of service quality (Reliability, Assurance, Tangibles, Emphaty, Responsiveness). Keywords. Satisfaction Level, KB Acceptors, MKJP Abstrak. Metode kontrasepsi yang semakin banyak dibahas adalah metode kontrasepsi jangka panjang, yang menawarkan keamanan, efektivitas, dan kenyamanan. Namun, pelaksanaan pelayanan KB masih belum optimal, terlihat dari rendahnya partisipasi dalam MKJP. Prevalensi penggunaan MKJP menurut data baseline SDKI tahun 2019 sebesar 21,39% sedangkan target RPJMN tahun 2024 sebesar 28,39%. Hal yang mempengaruhi partisipasi dalam mengikuti KB adalah kepuasan akseptor terhadap pelayanan fasilitas kesehatan. Penelitian ini dilakukan untuk mengetahui gambaran tingkat kepuasan akseptor KB terhadap layanan MKJP. Penelitian ini menggunakan jenis penelitian deskriptif kuantitatif. Jumlah sampel dalam penelitian ini sebanyak 56 responden Putri Usia Subur (WUS), pengumpulan data diperoleh dengan menggunakan kuesioner yang dibagikan kepada WUS yang mendapatkan layanan KK berencana MKJP di Puskesmas Poasia, data yang diperoleh akan dianalisis menggunakan SPSS versi 24 berupa tabel distribusi frekuensi. Temuan penelitian ini mencakup tingkat kepuasan dalam kategori "sangat puas" untuk dimensi keandalan (83,2%), dimensi Jaminan (85,4%), dimensi Tangibles (86,9%), dimensi empati (85,5%), dan dimensi responsif (85%). Secara keseluruhan, ibu-ibu yang mendapatkan pelayanan KB MKJP di Puskesmas Poasia merasa "sangat puas" (85,4%) dengan pelayanan yang diberikan dengan memperhatikan lima dimensi kualitas pelayanan (Reliability, Assurance, Tangibles, Emphaty, Responsiveness). Kata kunci. Tingkat Kepuasan, Akseptor KB, MKJP